Методичні підходи навчання математики іноземних студентів у вишах агротехнологічного профілю - Сосницька, Наталя Леонідівна; Сосницкая, Наталья Леонидовна; Sosnytska, Natalia; Кравець, Василь Іванович; Кравец, Василий Иванович; Kravets, Vasyl; Кравець, Олена Олександрівна; Кравец, Елена Александровна; Kravets, Olena (My University, 2017)
UK: У статті запропоновано методичні підходи навчання математики іноземних студентів на факультеті довузівської підготовки на основі використання викладачем мови-посередника. Відповідно цьому підходудовузівська підготовка з математики здійснюється у три етапи (перший та другий початковий, повторювальний), після яких студенти повинні на високому рівні вільно володіти математичною лексикою українською мовою і вміти самостійно вести записи під час лекційних та практичних занять. Запропоновано систему практичних завдань на основі мови-посередника зорієнтовану на формування математичних компетенцій. RU: В статье предложены методические подходы обучения математики иностранных студентов на факультете довузовской подготовки на основе использования преподавателем языка-посредника. Соответственно этому подходу довузовская подготовка по математике осуществляется в три этапа (первый и второй начальные, повторяющий), после прохождения этих этапов студенты должны на высоком уровне свободно владеть математической лексикой украинского языка и уметь самостоятельно производить записи во время лекционных и практических занятий. Предложено систему практических заданий на основе языка-посредника ориентированную на формирование математических компетенций. EN: The problem of teaching mathematics to foreign students at agrotechnological universities is considered in the paper. Mathematics is one of the first subjects which have been teaching during the first and second course of studying at university. Based on the experience of teaching mathematics in agrotechnological universities it was founded that foreign students enter the faculty of pre-university training of agrarian area having different level of knowledge and absolute absence of motivation to studying mathematics. It is necessary for students of all specialties to have an ability of analyzing, generalizing of statistic material, interpreting situation correctly. Available didactic and methodological material bases on the methodology of teaching mathematics to Ukrainian students of secondary schools and enrollees cannot be used by foreign students, so it needs special review and adaptation. For solution of this problem the authors suggested the methodological approaches of teaching mathematics to foreign students studying at the faculty of pre-university training based on the using of language-mediator. According to this approach the pre-university stage is realized in three steps (first, second and final), which lead to high level of proficiency in mathematical and Ukrainian vocabulary, the improvement of writing and listening skills. The proposed system of practical lessons bases on lecturer using the language-mediator provides for lecturer understanding of phonetic and lexical difficulties, which students meet during the studying at the first stage. On this basis lecturer should speak slowly, clearly, using the previously studied lexical material; it is admitted speaking students’ native language. In this case it’s necessary to pay attention to the lecturer’s level of foreign language, it should be not below B2. It will be useful to coordinate the process of teaching foreign students with lecturers of Ukrainian language, choosing the studying material for lectures and practical lessons.
Методические подходы обучения математики иностранных студентов в вузах агротехнологического профиля
Methodological approaches of teaching mathematics to foreign students at agrotechnological universities
Keywords: навчання математики; методичні підходи; довузівська підготовка; іноземні студенти; агротехнологічний профіль; обучение математике; методические подходы; довузовская подготовка; иностранные студенты; агротехнологический профиль; teaching mathematics; methodological approaches; pre-university training; foreign students; agrotechnological universities